Analysis Of The Influence Of Digital Marketing, Content Marketing, And Sponsorship On Brand Awareness - Pripinda, Ayuneira Dega; Paramitha, Dyah Ayu (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : The purpose of this study is to analyze the influence of digital marketing, content marketing, and sponsorship on brand awareness in national export schools.Design/Methode/Approach : Quantitative research methods were used for this study, utilizing observations, interviews, and questionnaires for data collection. Statistical analysis, including hypothesis testing, determination coefficients, validity tests, reliability, normality, heteroskedasticity, multicollinearity, linear regression, bwr, t-test, f test, determination coefficient, was carried out using SPSS 40.Research Finding : This study reveals that digital marketing, content marketing, and sponsorship, greatly affect brand awareness for target markets or prospective students and students of the National Export School. Based on the validity test, normality, heteroscedasticity, multicollinearity, linear regression, multiple tests, t test, f test, determination coefficient, showed a positive influence.Theoretical contribution/Originality : This study contributes to the existing literature by showing the importance of digital marketing, content marketing, and sponsorship to brand awareness. This is in line with previous research that emphasized the importance of factors such as digital marketing, content content marketing, social media, and promotions in creating brand awarenessPractitionel/Policy implication : The findings of this study can be used by companies to develop more focused marketing strategies, utilizing digital marketing, content marketing, and sponsorship to increase brand awareness. This research also provides insight into the effectiveness of using digital platforms in increasing brand visibility, so that companies can be more optimal in utilizing digital tools.Research limitation : This research is limited to prospective students, students, and alumni of the National Export School who receive JJE International Sponsorship